How Much Loading Does Water Resistance Voice Therapy Impose on the Vocal Folds? An Experimental Human Study - Laukkanen, Anne-Maria; Geneid, Ahmed; Bula, Vítězslav; Radolf, Vojtěch; Horáček, Jaromír; Ikävalko, Tero; Kukkonen, Tarja; Kankare, Elina; Tyrmi, Jaana (Journal of voice, 2020)
OBJECTIVES: Water resistance voice therapy applies phonation into water through a tube. This study investigates how strenuous this therapy can be for the vocal folds in terms of impact stress (IS). It further examines whether it is possible to estimate the IS using the contact quotient (CQ) and maximum derivative from an electroglottogram (EGG). STUDY DESIGN: Experimental study. METHODS: A male participant sustained a rounded back vowel [u:] or [o:] at a comfortable speaking pitch and loudness, and phonated into a silicone "Lax Vox" tube submerged 2 cm in water. High-speed videolaryngoscopy was performed with a rigid scope. Oral air pressure (Poral) was registered in a mouthpiece through which an endoscope was inserted into the larynx. An EGG was recorded. RESULTS: The CQEGG from the EGG and the closed quotient from the glottal width (CQarea) increased, while the maximum glottal amplitude and absolute value of derivative minimum (dmin) and also the derivative maximum from the EGG decreased for phonation into water. Normalized amplitude quotient from the glottal width variation also decreased but the change was not significant. CONCLUSIONS: Based on the glottal area findings, water resistance therapy does not seem to increase vocal fold loading (in terms of increased IS) even if the increase of CQarea, and CQEGG suggest so. CQEGG may qualitatively correspond to that of area, but the reliability of CQ (from the glottal area or the EGG) and the maximum derivative from the EGG as estimates of IS in semiocclusion exercises warrant further studies.
Keywords: dospělí; hlasové řasy; Impact stress; hlasový trénink; Biomechanics; elektrodiagnostika; Voice Training; Adult; Time Factors; časové faktory; lidé; tlak; Oral pressure; laryngoskopie; Vocal Cords; Laryngoscopy; Electroglottogram; Speech Acoustics; Video Recording; voda; Electrodiagnosis; biomechanika; High-speed imaging; Water; Male; Phonation; akustika řeči; fonace; audiovizuální záznam; mužské pohlaví; Voice Quality; kvalita hlasu; Voice therapy; Biomechanical Phenomena; Pressure; Humans